La planificación estratégica en la gestión de la empresa “La clínica del automóvil” en la ciudad de Riobamba - Juan Carlos, Castañeda Castañeda (2021)
ABSTRACT The present research work that was carried out on strategic planning deals with a management tool that allows the organization to achieve its objectives; therefore, the strategic guideline is directly related to the formulation of the mission, vision, values, objectives, and strategies that every company must have under different parameters. The main purpose of this work is STRATEGIC PLANNING IN THE MANAGEMENT OF THE COMPANY "LA CLÍNICA DEL AUTOMÓVIL" IN THE CITY OF RIOBAMBA. At present, this tool must be used by all companies; however, it has been confirmed that several companies do not apply strategic plans, which manage their businesses empirically "tacit knowledge", that is; without having full technical knowledge of why they exist and why they exist, what are their strengths, weaknesses and in which of them they should make improvements, being not very susceptible to market changes and very weak when growing as a company. When knowing the problems of the company through surveys and different interviews; It is eminent that one of the primary objectives is to design strategic planning, to improve its empirical management, where it will contain a series of ordered steps that must be applied in the company to progress in a certain time and not late. With this research, it is expected to contribute to the improvement of the automobile clinic company through a proposal that compensated all its questions, which aims to consolidate its growth within an increasingly competitive and demanding market. Keywords: strategic guidelines, planning, innovation, quality service. Reviewed by: Mgs: Sonia Granizo Lara. ENGLISH PROFESSOR. C.C. 0602088890